Neonatal Serum Phosphorus Levels and Enamel Defects in Very Low Birth Weight Infants. (August 2016) - Merheb, Roula; Arumugam, Chitra; Lee, Wonik; Collin, Marc; Nguyen, Caroline; Groh-Wargo, Sharon; Nelson, Suchitra
Background: Very low birth weight (VLBW) infants miss out on the period of greatest mineral accretion that occurs during the last trimester of pregnancy and are at higher risk of enamel defects. No studies have well described the relationship between neonatal nutrition and dental outcomes in preterm, VLBW infants. The objective of this study was to assess the differences in nutrition biomarkers, feeding intake, and comorbidities among VLBW infants with and without enamel defects. Methods : A retrospective chart review of VLBW infants recruited for an ongoing longitudinal dental study between 2007 and 2010 was done. Participants were classified as cases and controls according to the presence/absence of developmental defects of enamel at 8 and/or 18–20 and/or 36 months. Demographics and medical and nutrition data were abstracted from 76 subjects' medical charts. Results : Of the 76 VLBW subjects, 62% had enamel defects (hypoplasia and/or opacity). The only significant variable in the logistic regression analysis was that infants with a 1-mg/dL increase in serum phosphorus levels had a 68% reduction in the odds of having enamel hypoplasia (odds ratio, 0.322; P = .024). Conclusion : Neonatal lower serum phosphorus levels are significantly associated with enamel hypoplasia in VLBW infants younger than 3 years.